Carbon Tax Versus Renewable Energy Innovation: Theoretical Insights and Empirical Evidence - Roy, A.; Chen, Pu; Semmler, W. (2025)
In European countries, carbon pricing is often viewed as a primary strategy to combat climate change and climate risks by reducing carbon emissions and driving investment into cleaner energy sources. Decarbonization has also been suggested by directed technical change, which implements innovative renewable energy technology. We study the effectiveness of both policies for selected Northern EU countries. In a model-based investigation, we first compare optimizing and behavioral drivers of decarbonization with a focus on the two decarbonization policies. Econometrically we use local projection and the VAR method to explore the effects of both policies, carbon tax and directed technical change on GDP and emission reduction. Our results show that—although both policies are needed–significant technology-oriented policy actions on the supply side of renewable energy appear to be required to accelerate the decarbonization of the economies.